Trichosanthes napoensis (Cucurbitaceae), a new species from Guangxi, China - Nong, Dong-Xin; Huang, Bao-You; Lan, Zu-Zai; Xie, Dong Mei; Yu, Li-Ying; Huang, Lu Qi (Phytotaxa, 2015)
A new species of the genus Trichosanthes (Cucurbitaceae), T. napoensis, is described and illustrated from Guangxi Province, western China. It is closely related to T. pedata Merr. & Chun, but it can be distinguished from the latter by having 3-fid tendrils, a fruit apex with a prominent protrusion, and oblong-elliptical seeds with a ridge at the margin.